PELAKSANAAN PEMASANGAN IMPLANT PADA PASANGAN USIA SUBUR DI UPTD PUSKESMAS RI RAJABASA LAMPUNG SELATAN - Anna Dwi Wulandari; Yona Desni Sagita; Yesi Yuniasari; Eka Noviana; Budi Trisnawati; Maya Fadilah (Kirana Publisher, 2024)
Implants are a long-term family planning method (MKJP). This contraceptive requires skills in removing and installing it. An implant is a type of Long Term Contraceptive Method (MKJP) which is in the form of a small rod that is placed under the skin layer of the inner upper arm. The implant contains the hormone progesterone which can be effective for three years and can return to fertility after the removal process (BKKBN, 2020). According to the BKKBN, implants are one strategy for family planning services to accelerate the reduction in the Total Fertility Rate (TFR) in Indonesia. Based on its use, implants are more efficient because they are used for a long time and are safer and more effective. The MKJP failure rate is reported to be 0.2 per 1000 users, while non-MKJP methods are reported to occur at 10 per 1000 users (BKKBN, 2020). . The implementation of this community service activity was attended by 10 women of childbearing age in the working area of the Rajabasa Community Health Center. The method used in this activity was through lectures and discussions as well as questions and answers about contraceptives and continued with implant installation. This activity increases knowledge of women of childbearing age about implants while increasing MKJP coverage in the family planning sector